Adjustment of air line structure for optimal transport management and electricity distribution - Cherkashyna, Veronika (Technology audit and production reserves, 2017)
The object of research is processes in air lines that affect the transportation and distribution of electricity. One of the most problematic places is the wires of overhead lines. The variety of wires with which the lines are made leads to heterogeneity of the network, which is reflected in the technological losses of power. In the course of the study, the technical and economic model of discounted costs in air lines is used, which is improved due to a change in the analytical connection of investments with wire cross-section. A criteria method is used to analyze this model. This method allows to analyze such models and to make a decision in relative units with incomplete initial information. It is received that perfection of structure of overhead lines at the expense of optimization of parametrical series of sections of wires allows to reduce influence of heterogeneity of a network. And also to proceed to the unification of overhead lines, to increase the schedule for the reconstruction of the facility, but does not expand the functionality of the lines. Equipping the lines with a fiber-optic monitoring system allows to monitor the parameters of the object along the entire length of the object. This reduces the loss of active power and provides an opportunity to optimally manage the transport and distribution of electricity in real time. The proposed direction has a number of features, in particular, shows a consistent improvement in the structure of the lines. In comparison with similar known approaches, the advantage of the proposed approach is the complex justification of the development of overhead lines in the electricity market.